IMPROVING THE CHARACTERISTICS OF LLC CONVERTERS USING THE METHOD OF HYBRID HYSTERESIS CONTROL - CHAPLIY, DMYTRO; BABIUK, SERGIIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In today’s world of high-tech, advanced electronic systems such as multi-processor modules and System-on-Chip (SoC) systems form the foundation for breakthroughs in future information technology and power efficiency. However, the rapid growth of complexity and functions in such systems leads to an increase in energy consumption, which in turn seriously limits the miniaturization, efficiency, reliability and service life of such systems. Various methods are used to manage energy consumption. Pulsed high-frequency power converters are considered the best option due to their high efficiency and good dynamic characteristics. In addition, the non-linearity of the characteristics of impulse power converters allows them to work in a wide range of operating conditions, under different loads and voltage changes in the network. However, only one control scheme, such as pulse width modulation (PWM), cannot optimize the entire system complex in different scenarios. Therefore, hybrid control schemes are used in power converters that work together and continuously to ensure performance during all periods of operation: start-up, operating mode and dynamic loads. Research into advanced control methods for LLC converters has been analyzed, describing modern LLC operation methods such as Bang-Bang Charge Control (BBCC) and Time-Shift Control (TSC). An innovative method, Hybrid Hysteresis Control (HHC), ensures excellent transient response characteristics by simplifying the LLC converter power stage into a single-pole system, which is easier to compensate with increased bandwidth. Additionally, this method provides excellent elimination of AC current ripple by directly controlling the total input power supplied to the secondary winding of each switching cycle. Eliminating AC current ripple allows developers to meet strict output voltage requirements with smaller PFC output capacitor capacity, thereby reducing the cost and board size of the final product.